Sophorolipids Production by Candida bombicola ATCC 22214 and its Potential Application in Microbial Enhanced Oil Recovery - Elshafie, Abdulkadir E.; Joshi, Sanket J.; Al-Wahaibi, Yahya M.; Al-Bemani, Ali S.; Al-Bahry, Saif N.; Al-Maqbali, Dua’a; Banat, Ibrahim M. (Frontiers in Microbiology, 2015)
Biosurfactant production using Candida bombicola ATCC 22214, its characterization and potential applications in enhancing oil recovery was studied at laboratory scale. The seed media and the production media were standardized for optimal growth and biosurfactant production. The production media were tested with different carbon sources: glucose (2%w/v) and, corn oil (10%v/v) added separately or concurrently. The samples were collected at 24h interval up to 120h and checked for growth (OD660), and biosurfactant production (Surface tension and Interfacial tension). The medium with both glucose and corn oil gave better biosurfactant production and reduced both surface tension and interfacial tension to 28.56 + 0.42mN/m and 2.13 + 0.09mN/m, respectively within 72h. The produced biosurfactant was quite stable at 13-15% salinity, pH range of 2-12, and at temperature up to 100°C. It also produced stable emulsions (%E24) with different hydrocarbons (pentane, hexane, heptane, tridecane, tetradecane, hexadecane, 1-methylnaphthalene, 2,2,4,4,6,8-heptamethylnonane, light and heavy crude oil). The produced biosurfactant was extracted using ethyl acetate and characterized as a mixture of sophorolipids. The potential of sophorolipids in enhancing oil recovery was tested using core-flooding experiments, under reservoir conditions, where additional 27.27% of residual oil (Sor) was recovered. This confirmed the potential of sophorolipids for applications in microbial enhanced oil recovery.